Fiscal Policy and the Predictability of Exchange Rate Collapse - Daniel, Betty (IMF Working Papers; Working Paper, 1997)
It is well known that the long-run viability of a fixed exchange rate regime imposes constraints on monetary policy. This paper shows that, in a model with forward-looking agents, short-run viability imposes a fiscal constraint. When policy change, which destroys long-run viability, also violates the fiscal constraint, collapse is instantaneous. Delayed predictable collapse requires satisfaction of the fiscal constraint.